2017
DOI: 10.3390/molecules22040565
|View full text |Cite
|
Sign up to set email alerts
|

Ergosteryl 2-naphthoate, An Ergosterol Derivative, Exhibits Antidepressant Effects Mediated by the Modification of GABAergic and Glutamatergic Systems

Abstract: Phytosterols are a kind of natural component including sitosterol, campesterol, avenasterol, ergosterol (Er) and others. Their main natural sources are vegetable oils and their processed products, followed by grains, by-products of cereals and nuts, and small amounts of fruits, vegetables and mushrooms. In this study, three new Er monoester derivatives were obtained from the reflux reaction with Er: organic acids (furoic acid, salicylic acid and 2-naphthoic acid), 1-Ethylethyl-3-(3-dimethyllaminopropyl) carbod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The authors showed that the antidepressant-like effects of this plant extract were produced by the flavonoid luteolin through actions on the GABA A receptor. Such GABA A receptor activation has also been involved in the antidepressant-like activity of other plant metabolites [ 82 , 83 ] and some neurosteroids such as allopregnanolone [ 84 86 ].…”
Section: Antidepressant-like Effects Of Flavonoids In Plant Extracmentioning
confidence: 99%
“…The authors showed that the antidepressant-like effects of this plant extract were produced by the flavonoid luteolin through actions on the GABA A receptor. Such GABA A receptor activation has also been involved in the antidepressant-like activity of other plant metabolites [ 82 , 83 ] and some neurosteroids such as allopregnanolone [ 84 86 ].…”
Section: Antidepressant-like Effects Of Flavonoids In Plant Extracmentioning
confidence: 99%
“…The FST was performed, according to the procedure described previously, in order to assess the behavioral despair of the mice [53]. The mice were forced to swim for 6 min individually in an open cylinder-shaped flask (height 25 cm, diameter 10 cm) with 15 cm of fresh water at 23–25 °C.…”
Section: Methodsmentioning
confidence: 99%
“…A monoamine hypothesis has been proposed to elucidate the pathogenesis of this disease. It assumes that reduction of the level of monoamine transmitters in the CNS, e.g., 5-HT, NA, and DA, is responsible for the development of depression [54,[77][78][79][80]. Dopamine deficiency in the CNS may be a cause of depression and "foggy brain" [81].…”
Section: Neurotransmitters As the Key Pathogenetic Factorsmentioning
confidence: 99%